Analysis of landslide area of Tulung subdistrict, Ponorogo, Indonesia in 2017 using resistivity method. Issue 4 (22nd May 2020) - Susilo, Adi; Fitriah, Fina; Sunaryo,; Ayu Rachmawati, Eng Turniningtyas; Suryo, Eko Andi
Abstract : Purpose: Research has been conducted to analyze the landslide in Banaran area, Ponorogo Regency. The landslides occurred on April 1, 2017. This study was conducted to know the subsurface conditions in the Banaran area to analyze the disaster mitigation efforts. The mitigation efforts are made to reduce the risk from landslides and possible landslides. Design/methodology/approach: The method used is the geo-electric resistivity method of Wenner–Schlumberger configuration. The research was conducted in three villages namely Banaran Village, Bekirang Village and Mendak Village. Findings: There are 12 resistivity measuring points with a track length of 410 m and a space of 10 m. The measured resistivity range is between 1.42 Ω.m and 67.500 Ω.m. The resistivity data and the local geological maps interpreted that the rocks in the Banaran area consist of clay, tuff lapilli, volcanic breccia and andesite lava. The landslide area begins at a depth of 8–35 m below the surface which is interpreted as tuff. Also, the thickness of the landslide material and the slope is = 400 which supports the occurrence of a more prominent landslide. The results of the parameter scoring of the landslide-prone areas indicated that the research area is very vulnerable to a landslide. The results of the interpretation indicate that the geo-electric resistivity method can provide a good overview for conducting landslide analysis, that is field slippage and potential material thickness occurrence landslide. Originality/value: This article is very specific as it attempts to discover how prone Banaran are is to landslide.